KH. Ahmad Dahlan and KH. Imam Zarkasyi about Islamic Education - Mamluatul Hasanah (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2024)
At the beginning of the 20 th century, muslim people thought that they would be considered infidels if their children were sent to dutch east indies gofernment schools which used the western system, namely wearing trousers, suits, ties and so on. This assumption has a major influence on the muslim economy, resulting in muslim communities not having access to government sectors and private companies. To improve the educational conditions of muslims in indonesia, especially muslims, one of the reform figures, namely KH Ahmad Dahlan, founder of the muhammadiyah organisation in 1912, who came from kauman yogyakarta, was also famous as asocial and religious activist, offering a new education system by collaborating religious knouledge and general acience. According to him, only through education like this, the condition of muslims in indonesia can develop better in terms of economics and economic education. Then KH. Imam zarkasyi also reformed islamic education which was divided into four groups. These include, in the fields of educational methods and systems, islamic boarding school structure and management, islamic boarding school curriculum as well as islamic boarding school mindset and freedom.